Colloid cyst: unusual location of petrous temporal bone - Chatterjee, Sunayana; Rokade, Vishal; Mali, Sahil Rajesh (International Surgery Journal, 2020)
Colloid cysts are benign, thin walled spherical neoplasms, composed of a collagenous capsule, underlying epithelium that arises from brain’s epidermal embryonic remnants and a viscous centre. They are shown to approximate 0.5% of all intracranial tumours with no recorded evidence of the petrous temporal bone involvement. Colloid cyst of the petrous temporal bone often presents with clinical symptoms of headache, hearing loss, facial palsy and imbalance/vertigo. Which is diagnosed on radiological and histological findings. Histologically, they are lined by ciliated cuboidal to pseudo stratified columnar epithelium resting on an eosinophilic basement membrane. Imaging Techniques are helpful in early diagnosis and preventing further complications. Here we will be discussing about a 24-year-old female, a known case of petrous apex osseous haemangioma presenting with unstable gait and tingling sensation on one side of face leading to an incidental finding of a colloid cyst on petrous temporal bone through histological examination.